(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
هدفت هذه الدراسة إلى تعقب سلوكيات الكادميوم والرصاص في تربة بازلتية لها مكانتها في البيئة السورية. وتم ذلك "بحضن" التربة في أصص بعد إضافة العنصرين منفصلين بمعدل 10 ppm للكادميوم و 30 ppm للرصاص. استمرت التجربة ثلاثة أشهر، تخللها اعتيان متتابع للكشف عن الشكل الذائب–المتبادل، والمرتبط بالكربونات، والمرتبط بالأكاسيد إضافة إلى القابل للامتصاص، وذلك بواسطة استخلاص "متوازٍ" استخدمت فيه "المستخلصات": كلوريد المغنيزيوم، وخلات الصوديوم، والهيدروكسيل أمين، ثم الـ DTPA. أكدت النتائج أن للمستخلصات الثلاثة الأولى طاقة استخلاص متدرجة، وأظهرت سهولة استخلاص الكادميوم، الذي يدل مساره الحركي على تحول الشكل المتبادل إلى مرتبط بالكربونات والأكاسيد، ولكن مع بقاء نسبة هامة منه بصورة تبادلية. وأما الرصاص فقد أبدى ثباتاً ومقاومة للاستخلاص، وأظهر مساراً يدل على أن الأكاسيد قد لا تكون الركيزة المفضلة لربطه، بل الطور الكربوناتي. وأكدت النتائج أيضاً أن للمعدنين سلوكين مختلفين، يبقى الكادميوم بمحصلتهما أكثر قابلية للحركة في النظام البيئي وأشد خطورة فيه، دون أن يعني ذلك إغفال الخطورة السمية للرصاص، ذلك أن المستخلَص منه بالـ DTPA لا يستهان به أيضاً. An incubation "pot" experiment for three months was conducted to assess the kinetic transformation, and repartition of cadmium and lead among bioavailable, soluble-exchangeable, carbonate bonded and Fe-Mn oxides bonded forms in basaltic soil receiving 10 and 30 ppm of Cd and Pb, respectively. Results from parallel extraction showed high extractability of Cd, and indicated that the dominant soluble-exchangeable Cd during the first stages was partially transformed with time into carbonate bonded and especially into Fe-Mn oxides bonded forms. Nonetheless, the label soluble-exchangeable Cd portion remained important. As compared with cadmium, lead appeared much less extractible, more stable, and conducted a likely different kinetics. Although indications supported higher mobility for Cd, both metals seemed to be potentially hazardous since that the DTPA test showed that both Cd and Pb are bioavailable. It was additionally noticeable that the DTPA test correlated significantly with NaOAc extraction, especially in the case of Cd.